Effectiveness of the Education Program on Using Iodine Mouthwash on Dental and Oral Health in Adolescents: An Intervention Study in the Adolescent Community in Batusangkar City, Indonesia - Aini, Rahmatul; Harfindo Nismal; Desy Purnama Sari; Dyana Putri (HM Publisher, 2024)
Poor oral health in adolescents is a significant public health problem in Indonesia. Iodine-based mouthwash has been proven effective in reducing plaque and gingivitis, but its use is not optimal among adolescents. This study aims to evaluate the effectiveness of an educational program on the use of iodine-based mouthwash on dental and oral health among adolescents in Batusangkar City. This research is an experimental study with a pre-post test design involving 150 adolescents aged 12-18 years in Batusangkar City. Participants were randomly divided into an intervention group (receiving an educational program and iodine mouthwash) and a control group (receiving an iodine mouthwash). Plaque index, gingival index, and knowledge about dental and oral health were measured before and after the intervention for 6 months. Data analysis was carried out using paired t-tests and independent t-tests. There was a significant reduction in plaque index and gingival index in the intervention group after 6 months of intervention (p < 0.05). The increase in knowledge about dental and oral health was also significant in the intervention group (p < 0.05). There were no significant differences between the two groups at the start of the study. The educational program on the use of iodine-based mouthwash is effective in improving dental and oral health among adolescents in Batusangkar City. This program can be recommended as part of efforts to prevent dental and oral diseases in adolescents.